Diverse Misfolded Conformational Strains and Cross-seeding of Misfolded Proteins Implicated in Neurodegenerative Diseases - Lim, Kwang Hun (Frontiers in Molecular Neuroscience, 2019)
Numerous neurodegenerative diseases including prion, Alzheimer’s and Parkinson’s diseases are characterized by accumulation of protein aggregates in brain. Prion disease is unique in that the natively folded prion protein forms diverse misfolded aggregates with distinct molecular conformations (strains), which underlie different disease phenotypes. In addition, the conformational strains are able to self-propagate their unique conformations by recruiting normal protein monomers and converting their conformations to misfolded conformers. There is an increasing body of evidence that suggests other aggregation-prone proteins including tau and α-synuclein associated with Alzheimer’s and Parkinson’s diseases, respectively, also behave like a prion that has conformational strains with self-propagation (seeding) property. Moreover, misfolded protein aggregates can promote misfolding and aggregation of different proteins through cross-seeding, which might be associated with co-occurrence of multiple neurodegenerative diseases in the same patient. Elucidation of diverse conformational strains with self-propagation capability and of molecular basis for the cross-talk between misfolded proteins is essential to the development of effective therapeutic intervention.